Analysis of the potential implementation of a methane-based carbon tax in the livestock sector in Indonesia - Salsabilla, Anindita Rahma; Dinarjito, Agung (Educoretax, 2024)
As one of the contributors to greenhouse gas emissions, methane emissions produced by the livestock sector are something that must be addressed immediately. A carbon tax could be one option that can be implemented to overcome this problem. This research aims to discuss whether there is potential to implement a methane-based carbon tax in the livestock sector in Indonesia. This research uses a qualitative approach with a systematic literature review and uses the PRISMA method. The literature used is publications published from 2020 to 2024. Research shows that there is potential for implementing a methane-based carbon tax and there is potential for implementing a carbon tax in the livestock sector. It is hoped that this research will provide clarity regarding the potential for implementing a carbon tax in Indonesia and become a reference for other studies in the future. The limitation of this research is that there has not been a comparison of ideal practices in implementing methane-based carbon taxes in other countries with existing regulations in Indonesia.